Physiological Study of Two Ectomycorrhizal Fungi Isolated from Kumaun Himalaya - Yadav, Anurag; Yadav, Kusum (Indian Forester, 2012)
Two dominant ectomycorrhizal (ECM) fungal species viz Cantharellus cibarius and Scleroderma bovista were isolated from respective mushrooms from Nainital hills of Uttarakhand, India. These fungi were extensively studied for three physiological parameters 0 viz temperature, pH and NaCl concentration. Temperature of 10, 15, 20, 25, 30 and 35°C, pH of 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5 and 8.0 and NaCl concentration of 10, 20, 30, 40, 50 and 60 was used to find the optimum growth of these ECM fungi. Temperature 0 of 25 C was found optimum for the growth of C. cibarius and S. bovista. Optimum pH was obtained at 5.5 for S. bovista and 5.0 for C. cibarius (at 25°C, optimum temperature). Presence of NaCl in small amounts somewhat enhanced the fungal growth. Concentration of 30 mM NaCl produced maximum mycelial dry wt of S. bovista (173.6 mg) and 40 mM for C. cibarius (58.4 mg) (after 36 days of incubation at 25°C), significantly higher than control (0 mM).